Pemberdayaan Masyarakat Dalam Pengelolaan Hewan Kurban Yang Halal Dan Baik Di Masjid Baiturrahman - Azzahra, Sitti Aliyah; Saefullah, Aep; Tohiroh, Tohiroh; Abas, Farhat; Rifia, Tetty Nur Intan; Zainuddin, Zulkifli; Putra, Idrisi Raliya; Nurhayati, Nurhayati; Nurhakim, Rahman; Hidayatullah, Syarif; Saputri, Haria; Tahang, Moh (LPPM STIE Ganesha, 2024)
The Community Service conducted by LPPM STIE Ganesha focuses on the management of sacrificial animals, encompassing the entire process from slaughter to the packaging and processing of meat. The objective of this initiative is to enhance the skills and knowledge of the community and the management committee of DKM Masjid Baiturrahman, located at Jl. Legoso Raya No. 31B, RT 06 RW 07, Kelurahan Pisangan, District of East Ciputat, South Tangerang City, particularly regarding halal slaughter practices and the management of sacrificial meat packaging and processing. The methodology utilized by the service team involves direct education through explanations and demonstrations conducted indoors. This approach includes both technical demonstrations and theoretical explanations, with the expectation that they can be applied by the community and the management committee of DKM Masjid Baiturrahman in their daily practices. The outcomes of this community service initiative demonstrate an improvement in the community's understanding and skills related to halal slaughter practices and the processing of sacrificial animals. This improvement is evidenced by the participants' enthusiasm, active engagement in question-and-answer sessions, and participation in discussions by a significant number of DKM Masjid Baiturrahman's management committee. Furthermore, the initiative successfully fosters a spirit of mutual cooperation and collaboration within the community, which are fundamental values in the execution of sacrificial rituals. These activities are anticipated to enhance the management of sacrificial animals at Masjid Baiturrahman to be more effective, efficient, and compliant with religious and health standards